KEBIJAKAN PUNGUTAN EKSPOR CRUDE PALM OIL KELAPA SAWIT: PERKEMBANGAN DAN MEKANISME PEMUNGUTANNYA - Eka Intan Kumala Putri; Widyastutik Widyastutik; Amzul Rifin; Sri Hartoyo; Heny Daryanto (Departemen Agribisnis, FEM-IPB, 2008)
The rise of export tax of oil palm from 1.5% to 5.5% in the period of 2004-2006 was due to (a) the scarcity of cooking oil in the market; (b) the rise of cooking oil price in the domestic market; and (c) the scarcity of availability of domestic crude palm oil. The export tax of crude palm oil policy has long been a fiscal policy issued by the government of Indonesia since 1994. The export tax of crude palm oil has fluctuated, following the demand of crude palm oil in the international market. There is a pro and contra between farmers and the government in determining export tax of crude palm oil. In one hand, the farmers wish to have a very low level of export tax, while in the other hand the government wants to push the export tax at the highest level. This conflict of interest can no longer be solved so far by the crude palm oil stakeholders.